Impact of low-energy cosmic rays on star formation - Padovani, Marco; Ivlev, Alexei V.; Galli, Daniele; Offner, Stella S. R.; Indriolo, Nick; Rodgers-Lee, Donna; Marcowith, Alexandre; Girichidis, Philipp; Bykov, Andrei M.; Kruijssen, Diederik (Space science reviews, 2020)
In recent years, exciting developments have taken place in theidentification of the role of cosmic rays in star-forming environments. Observationsfrom radio to infrared wavelengths and theoretical modelling have shown thatlow-energy cosmic rays (<1 TeV$< 1\text{ TeV}$) play a fundamental role in shaping the chemical richness of theinterstellar medium, determining the dynamical evolution of molecular clouds. Inthis review we summarise in a coherent picture the main results obtained byobservations and by theoretical models of propagation and generation of cosmic rays,from the smallest scales of protostars and circumstellar discs, to young stellarclusters, up to Galactic and extragalactic scales. We also discuss the new fieldsthat will be explored in the near future thanks to new generation instruments, suchas: CTA, for the γ$γ $-ray emission from high-mass protostars; SKA and precursors, forthe synchrotron emission at different scales; and ELT/HIRES, JWST, and ARIEL, forthe impact of cosmic rays on exoplanetary atmospheres and habitability.
Gesehen am 16.04.2020